An Analysis of Politeness in Teacher's Utterances in an English Classroom - Risal Risal; Hanna Hanna; Tambunan Tambunan (Journal of Language Education and Educational Technology (JLEET), 2021)
The objectives of this research were three-fold: to explore the types of politeness uttered by the teacher, to analyze the most predominant type of politeness uttered, and to explore the strategies of politeness uttered by the teacher in an English classroom. This research employed a descriptive qualitative analysis. The subject of this research was an English teacher of MAN 1 Kolaka. This research was conducted with two cohorts; they were class XII.IA-2 and class XII.IA-4. The data were collected from three observations and recordings of teacher’s utterances. As many as 117 politeness utterances were identified, encompassing 55 positive politeness utterances, 45 negative politeness utterances, 6 bald on record utterances and 1 off record utterance. There were 17 strategies of politeness used by the English teacher. The most predominant type of politeness was positive politeness, including the strategies of exaggerating sympathy with the Hearer, which was used 3 times, including both the Speaker and the Hearer 6 times, giving gifts to Hearer 26 times, being optimistic 10 times, offering 2 times, notice attend to Hearer 4 times, using group identity mark 3 times, and Intensifying interest to the hearer 1 time.Keywords:Pragmatics, Politeness Strategies, Teacher’s Utterances, English Classroom